Musculoskeletal Disease in MDA5‐Related Type I Interferonopathy: A Mendelian Mimic of Jaccoud's Arthropathy. Issue 10 (22nd August 2017) - de Carvalho, Luciana Martins; Ngoumou, Gonza; Park, Ji Woo; Ehmke, Nadja; Deigendesch, Nikolaus; Kitabayashi, Naoki; Melki, Isabelle; Souza, Flávio Falcäo L.; Tzschach, Andreas; Nogueira‐Barbosa, Marcello H.; Ferriani, Virgínia; Louzada‐Junior, Paulo; et al.
Abstract : Objective: To define the molecular basis of a multisystem phenotype with progressive musculoskeletal disease of the hands and feet, including camptodactyly, subluxation, and tendon rupture, reminiscent of Jaccoud's arthropathy. Methods: We identified 2 families segregating an autosomal‐dominant phenotype encompassing musculoskeletal disease and variable additional features, including psoriasis, dental abnormalities, cardiac valve involvement, glaucoma, and basal ganglia calcification. We measured the expression of interferon (IFN)–stimulated genes in the peripheral blood and skin, and undertook targeted Sanger sequencing of the IFIH1 gene encoding the cytosolic double‐stranded RNA (dsRNA) sensor melanoma differentiation–associated protein 5 (MDA‐5). We also assessed the functional consequences of IFIH1 gene variants using an in vitro IFNβ reporter assay in HEK 293T cells. Results: We recorded an up‐regulation of type I IFN–induced gene transcripts in all 5 patients tested and identified a heterozygous gain‐of‐function mutation in IFIH1 in each family, resulting in different substitutions of the threonine residue at position 331 of MDA‐5. Both of these variants were associated with increased IFNβ expression in the absence of exogenous dsRNA ligand, consistent with constitutive activation of MDA‐5. Conclusion: These cases highlight the significant musculoskeletal involvement that can be associated with mutations in MDA‐5, and emphasize the value of testing for up‐regulation of IFN signaling as a marker of the underlying molecular lesion. Our data indicate that both Singleton‐Merten syndrome and neuroinflammation described in the context of MDA‐5 gain‐of‐function constitute part of the same type I interferonopathy disease spectrum, and provide possible novel insight into the pathology of Jaccoud's arthropathy.